1974
DOI: 10.2134/agronj1974.00021962006600010024x
|View full text |Cite
|
Sign up to set email alerts
|

Air Temperature and Vapor Pressure Changes Caused by Sprinkler Irrigation1

Abstract: The downwind effect of evaporation from sprinkler spray was studied in the field to determine if air temperature and vapor pressure were changed enough to influence plant growth and water use. Wet-bulb and dry-bulb temperature profiles were measured upwind and at three distances downwind from a sprinkler lateral before and during sprinkling. Wind-speed and direction were also measured. Air temperature generally was reduced less than 1 C, and vapor pressure in the air was increased less than 0.8 mb. This amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…For droplet diameters of 0.3 to 1.5 mm, Kincaid and Longely (1989) validated the sprinkler evaporation model pre sented in their paper against measurements using the micro needle syringe method presented in Kincaid (1989). Comparisons as related to droplet size and wind speed for simulated impact sprin klers operated at 414 kPa with 4.76 mm nozzles (Thompson 1993b Mclean et al (1994) as follows: Kohl and Wright (1974) and Dadiao and Wallender (1985) showed that sprinkler droplet size was propor tional to nozzle diameter. Hills and Gu (1989), Dadiao and Wallender (1985), and Edling (1985) found that the droplet size at any distance from the sprinkler is partially a function of the nozzle size.…”
Section: Water Source Temperature Effect On Spray Lossmentioning
confidence: 97%
“…For droplet diameters of 0.3 to 1.5 mm, Kincaid and Longely (1989) validated the sprinkler evaporation model pre sented in their paper against measurements using the micro needle syringe method presented in Kincaid (1989). Comparisons as related to droplet size and wind speed for simulated impact sprin klers operated at 414 kPa with 4.76 mm nozzles (Thompson 1993b Mclean et al (1994) as follows: Kohl and Wright (1974) and Dadiao and Wallender (1985) showed that sprinkler droplet size was propor tional to nozzle diameter. Hills and Gu (1989), Dadiao and Wallender (1985), and Edling (1985) found that the droplet size at any distance from the sprinkler is partially a function of the nozzle size.…”
Section: Water Source Temperature Effect On Spray Lossmentioning
confidence: 97%
“…The reason for these results may be that the pan at meteorological station is exposed to higher wind speed because it is placed 70 cm above ground surface. Other reasons may be the lower air temperature and vapor pressure deficit in the sprinkler irrigated fields as compared with those at meteorological stations due to the cooling evaporation of sprinkler water and transpiration of leaves (Kohl and Wright 1974;Kang et al 2002).…”
Section: Pan Coefficientmentioning
confidence: 99%
“…The reason for these results may be due to the fact that pan evaporation measured above top canopy used in methods A and B could represent the real field potential evaporation. The ET 0 computed by standard meteorological data used in method C may be not appropriately represent the field microclimatic condition in the sprinkler irrigated field because the temperature and humidity were significantly affected during sprinkler irrigation day and the following few days and in turn influence the actual ET (Kohl and Wright 1974;Kang et al 2002).…”
Section: Winter Wheat Evapotranspiration Estimationmentioning
confidence: 99%
“…In addition, Steiner et al (1983b) in one of the two studied years, and Liu and Kang (2006) reported that these microclimatic changes lasted for several days after the irrigation event. The microclimatic changes can also affect areas downwind from the irrigated area (Kraus, 1966; Kohl and Wright, 1974; Longley et al, 1983).…”
mentioning
confidence: 99%